2015
DOI: 10.1523/jneurosci.0296-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Theta Oscillations in Visual Cortex Emerge with Experience to Convey Expected Reward Time and Experienced Reward Rate

Abstract: The primary visual cortex (V1) is widely regarded as faithfully conveying the physical properties of visual stimuli. Thus, experienceinduced changes in V1 are often interpreted as improving visual perception (i.e., perceptual learning). Here we describe how, with experience, cue-evoked oscillations emerge in V1 to convey expected reward time as well as to relate experienced reward rate. We show, in chronic multisite local field potential recordings from rat V1, that repeated presentation of visual cues induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 59 publications
6
66
0
Order By: Relevance
“…The fact that default mode and salience networks are concurrently regulating and representing the internal milieu, while they are routinely engaged during a wide range of tasks spanning cognitive, perceptual, and emotion domains, all of which involve value-based decisionmaking and action 85 (e.g., [86][87][88] ; 29; for a review, see 87 ), suggest a provocative hypothesis for future research: whatever other psychological functions the default mode and salience networks are performing during any given brain state, they are simultaneously maintaining or attempting to restore allostasis and are integrating sensory representations of the internal milieu with the rest of the brain. Therefore, our results, when situated in the published literature, suggest that the default mode and salience networks create a highly connected functional ensemble for integrating information across the brain, with interoceptive and allostatic information at its core, even though it may not be apparent much of the time.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that default mode and salience networks are concurrently regulating and representing the internal milieu, while they are routinely engaged during a wide range of tasks spanning cognitive, perceptual, and emotion domains, all of which involve value-based decisionmaking and action 85 (e.g., [86][87][88] ; 29; for a review, see 87 ), suggest a provocative hypothesis for future research: whatever other psychological functions the default mode and salience networks are performing during any given brain state, they are simultaneously maintaining or attempting to restore allostasis and are integrating sensory representations of the internal milieu with the rest of the brain. Therefore, our results, when situated in the published literature, suggest that the default mode and salience networks create a highly connected functional ensemble for integrating information across the brain, with interoceptive and allostatic information at its core, even though it may not be apparent much of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiology. House-made 1.2 mm length 16-channel shank electrodes were implanted into binocular primary visual cortex (from Bregma: posterior, 2.8 mm; lateral, 3.0 mm; ventral, 1.2 mm) of adult mice, anesthetized with 2.5% isoflurane in 100% O2, as previously described (Murase et al, 2017;Zold and Hussain Shuler, 2015) . Animals received a single dose of Carprofen (5 mg/kg, SQ) for post-surgical analgesia after the return of the righting reflex.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that inactivation of the BF disrupts the global correlations of these cortical areas with other higher order cortical areas (Turchi et al, 2018). BF can also affect salience and reinforcement timing-related activity even in earlier sensory areas such as V1 (Shuler and Bear, 2006;Lin et al, 2015;Zold and Shuler, 2015). It is therefore likely that on a neuronal circuit level, stimulus-locked BF bursting may coordinate cortical activity in relation to external salient events.…”
Section: Discussionmentioning
confidence: 99%